2021
DOI: 10.1186/s12943-021-01475-8
|View full text |Cite
|
Sign up to set email alerts
|

The circular RNA circDLG1 promotes gastric cancer progression and anti-PD-1 resistance through the regulation of CXCL12 by sponging miR-141-3p

Abstract: Background Dysregulation of circular RNAs (circRNAs) plays an important role in the development of gastric cancer; thus, revealing the biological and molecular mechanisms of abnormally expressed circRNAs is critical for identifying novel therapeutic targets in gastric cancer. Methods A circRNA microarray was performed to identify differentially expressed circRNAs between primary and distant metastatic tissues and between gastric cancer tissues sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 75 publications
0
71
1
Order By: Relevance
“…Anti-programmed cell death protein 1 (PD-1) monoclonal antibody is a commonly used immune-checkpoint blockade agent for GC immunotherapy [ 116 ]. The circRNA circDLG1 facilitates GC progression and anti-PD-1 resistance via miR-141-3p -mediated the regulation of CXCL12 [ 106 ].…”
Section: Interplay Between Circrnas and Drug Resistance In Gcmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-programmed cell death protein 1 (PD-1) monoclonal antibody is a commonly used immune-checkpoint blockade agent for GC immunotherapy [ 116 ]. The circRNA circDLG1 facilitates GC progression and anti-PD-1 resistance via miR-141-3p -mediated the regulation of CXCL12 [ 106 ].…”
Section: Interplay Between Circrnas and Drug Resistance In Gcmentioning
confidence: 99%
“…Considering that circRNAs possess unique features such as tissue-and developmental stage-specific patterns, structural resistance to exonucleases and longer halflives, and specific circRNAs play essential roles in GC metastasis and drug resistance, manipulating circRNA abundance appears to be a promising therapeutic strategy for the advanced GC treatment [126-128, 131, 132]. Furthermore, combining circRNAs-based therapeutic interventions with traditional chemotherapy or targeted therapy offers a unique opportunity to conquer drug resistance in advanced GC patients [97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][113][114][115][116][117]. However, choosing crucial target circRNAs of interest is still a problem.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…To analyze the regulatory effect of Cas9 on its predicted binding microRNAs and their target genes, we first mined a database with the transcriptome characteristics of 331 cell lines overexpressing a Cas9 RNA and their parental control counterparts [12]. We also analyzed the binding possibilities between this Cas9 RNA and all the known human miRNAs using miRanda software [8]. The 51 miRNAs that were predicted to have the highest likelihood of binding Cas9 RNA were named "Cas9-miRNAs" (Fig.…”
Section: Cas9 Rna Could Affect Intracellular Gene Expression Through ...mentioning
confidence: 99%
“…A wide range of interactions between microRNAs (miRNAs) and mRNAs occur, not only in the 3′ untranslated regions but also in the amino acid coding sequences (CDSs) of mRNA [5,6]. An increasing number of research groups [7,8], including our team [9][10][11], recently found that a long RNA can bind and adsorb partially complementary miRNAs through a "miRNA sponge" mechanism, upregulating other target genes inhibited by these miRNAs. In this study, we investigated whether Cas9 RNA, an exogenous long-chain nucleic acid substance, could affect host cell gene expression through a miRNA sponge mechanism and developed an RNA sequence optimization strategy to improve the safety of this gene-editing system.…”
mentioning
confidence: 99%
“…CircIL4R competes with miR-761 to upregulate TRIM29 expression and promote CRC progression ( 6 ). In gastric cancer, high expression levels of circDLG1 were correlated with poor prognosis in immunotherapy-treated patients and promoted the migration, invasion, and immune escape of gastric cancer cells ( 7 ). Cancer stem cells (CSCs) are considered to underlie tumorigenesis, metastasis, and recurrence and have the characteristics of self-renewal and differentiation potential ( 8 ).…”
Section: Introductionmentioning
confidence: 99%